Building Inventory and Seismic Vulnerability Assessment of Government Office Buildings in Pokhara Metropolitan City - Dhakal, Amrita; DC, Dipesh; Bajracharya, Sujata Shakya (Journal of Engineering Issues and Solutions, 2026)
Government office buildings play a critical role in public service delivery and emergency response, yet their inventory and seismic performance remain insufficiently documented in many seismically active regions of Nepal. This study presents a comprehensive building inventory and preliminary seismic vulnerability assessment of 111 government office buildings (94 offices) located within Pokhara Metropolitan City, an area of high seismic hazard. The inventory documents key spatial, structural, architectural, and functional attributes of the buildings. The inventory indicates that the building stock is dominated by low to mid-rise reinforced concrete moment-resisting frame structures, with a substantial proportion constructed prior to the enforcement of the Nepal Building Code and several having undergone post-construction modifications. Seismic vulnerability was evaluated using two widely applied visual-inspection-based screening approaches: the Empirical Vulnerability Method and the FEMA P-154 Rapid Visual Screening method. Buildings were classified into vulnerability categories based on method-specific scoring frameworks, and results were compared at both aggregate and individual-building levels. Both screening methods consistently classify the majority of buildings within the low to moderate vulnerability categories, with no buildings identified as very highly vulnerable. However, FEMA P-154 generally yields more conservative vulnerability classifications compared to the empirical method, primarily due to fewer penalizing score modifiers. The building-wise comparison demonstrates strong agreement between the two approaches, with most buildings differing by no more than one vulnerability class.